Scientific Evaluation of A Unani Pharmacopoeia-Based Formulation on BPH in Animal Model - Dr. Mohammad Shujauddin; Shamshad Alam; Sumbul Rehman; Murad Ahmad, (International Journal of Preventive Medicine and Health (IJPMH), 2024)
BPH (Benign prostatic hyperplasia) is a common problem of the prostate gland that affects elderly men with age and major cause of lower urinary tract symptoms (LUTS) like urgency of urination, frequency of micturition, dysuria, nocturia, dribbling, and burning of urine. If left untreated, the condition can lead to severe urinary retention, recurrent UTI, and, in severe cases, renal failure, etc. Alpha-blockers and 5-alpha reductase inhibitors (5-ARIs) are two main classes of drugs that are used in conventional therapy to treat BPH. These phytochemical therapies are extremely effective, but standard control methods have unfavorable side effects too. Conversely, evidence, though limited, has shown that alternative medicines are safer and have the potential to improve LUTS and quality of life, in addition to improving sexual dysfunction in patients with BPH. The purpose of the study is to assess the efficacy of 50% hydroalcoholic UPBF extract on BPH in TP-induced rats, and the effects of the drug were compared between the treated and untreated groups. The experimental design for anti-BPH activity was carried out following the Bhavin model. 48 Wistar rats were divided into 6 groups, with 8 rats in each group. Group 1, plane control (untreated rats), group 2, negative control (treated with TP 5 mg/kg), group 3, negative control (treated with TP+ finasteride 1 mg/kg), and groups 4,5 and 6 served as tests controls (A, B, and C) treated with TP+ UPBF extract 100 mg/kg, 150 mg/kg, and 200 mg/kg as low, medium, and high doses, respectively. BPH was induced in rats by administration of testosterone propionate (TP) in arachis oil, and treatment was done orally with a standard drug (finasteride) and a test drug (UPBF) once a day for 28 consecutive days. Before and after initiating the study, each rat was weighed and documented, and after 28 days, the collection of blood samples and the prostate gland was done under light anesthesia. The parameters of the study were accessed, like prostate weight, prostate-to-body weight ratio, histopathological investigation of the prostate, percentage of inhibition, percentage of recovery, and determination of ST and STP levels. Data from the results were expressed as the mean ± standard error of the mean (SEM). Evaluation between group results was carried out with the one-way ANOVA test followed by Tukey’s test, and the significant value of p was <0.05. Both histopathological and biochemical parameter results showed significant improvements in rats treated with finasteride and UPBF extract at a dose of 200 mg/kg (p<0.001). In addition, ST and STP levels showed a significant reduction in comparison with the BPH group. It can be concluded from the findings of the results in both biochemicals and histopathological parameters that the test drug (UPBF) possesses significant effects against the TP-induced BPH in rats. The findings suggested that the test drug can be used independently in the management of BPH as well as for lower urinary tract symptoms.